1987
DOI: 10.1111/j.1476-5381.1987.tb10285.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of gastrin C‐terminal tetrapeptide (as pentagastrin) and cholecystokinin octapeptide in conscious rabbit and man

Abstract: 1 Pentagastrin and cholecystokinin octapeptide (CCK8) were infused i.v. at three different doses in two sets of 4 conscious rabbits following a repeated measurements design (130, 1,300 and 13,000 pmol kg-' min-' pentagastrin; 5, 50 and 450 pmol kg-' min-' CCK8). In man, two different doses of pentagastrin (13 and 65 pmol kg-' min-') were infused in two groups of 6 subjects, and CCK8 (2 pmol kg-' min-') in a third group. According to published human postprandial levels, plasma CCK8-like immunoreactivity concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Cholecystokinin also inhibits renal sympathetic vasomotor nerve activity via a vagal afferent mechanism (Koyama et al 1990). These sympathoinhibitory effects may play a role in the events that occur after a meal, increasing blood flow to the gut and kidney, to facilitate digestion and to deal with the additional fluid load, respectively (Calam et al 1987; Sartor & Verberne, 2002, 2008, 2010). The role of gut hormones in sympathetic withdrawal of vasomotor tone to these regions is likely to be important, because feeding can increase splanchnic blood flow as much as 150% and renal blood flow up to 100% from baseline (Premen, 1988), and collectively, these vascular beds can command more than half of the total cardiac output postprandially (Echtenkamp et al 1983).…”
mentioning
confidence: 99%
“…Cholecystokinin also inhibits renal sympathetic vasomotor nerve activity via a vagal afferent mechanism (Koyama et al 1990). These sympathoinhibitory effects may play a role in the events that occur after a meal, increasing blood flow to the gut and kidney, to facilitate digestion and to deal with the additional fluid load, respectively (Calam et al 1987; Sartor & Verberne, 2002, 2008, 2010). The role of gut hormones in sympathetic withdrawal of vasomotor tone to these regions is likely to be important, because feeding can increase splanchnic blood flow as much as 150% and renal blood flow up to 100% from baseline (Premen, 1988), and collectively, these vascular beds can command more than half of the total cardiac output postprandially (Echtenkamp et al 1983).…”
mentioning
confidence: 99%
“…In the absence of anaesthesia, pressor responses and sympathetically mediated generalised vasoconstriction have consistently been reported following systemic administration of CCK in conscious rats, dogs and guinea pigs (Bunting et al, 1997;Fossa et al, 1997;Janssen et al, 1991;Koszycki et al, 1998;Watanabe et al, 2004;Webb et al, 1996) although in rabbits, blood pressure fell (Calam et al, 1987). Tachycardia also accompanied the pressor response evoked in conscious dogs (Fossa et al, 1997;Janssen et al, 1991) although bradycardia was observed in guinea pigs (Fossa et al, 1997).…”
Section: Biasing Effects Of Anaesthesiamentioning
confidence: 90%
“…It is interesting to note that previous studies suggested an effect of CCK-related peptides in the kidney. Specifically, it has been shown that CCK-8, which interacts with CCK B receptors with high affinity, is able to cause changes in the glomerular filtration rate and in the renal blood flow in rabbit or man (Calam et al 1987;Duggan et al 1988;Unwin et al 1990). Studies using free-flow renal micropuncture in rats revealed that CCK-8 directly inhibits sodium and water transport in the loop of Henle (Unwin et al 1988).…”
Section: Discussionmentioning
confidence: 99%